PENGENDALIAN PENYAKIT TUBERKULOSIS PARU (P2TB) DI PUSKESMAS LABUHAN RATU KOTA BANDAR LAMPUNG - Fahrul Irayani (Jurnal Ilmu Kesehatan Masyarakat Indonesia (JIKMI), 2022)
Background: Indonesia is ranked 2nd with the highest TB sufferers in the world after India. Globally, 9.9 million people are estimated to have TB disease in 2020 and 10.6 million people with TB disease in 2021. According to the profile of the Bandar Lampung City Health Office, the number of TB sufferers (suspected found) in Bandar Lampung City was 17,810 sufferers. At the Labuhan Ratu Health Center it is known that the percentage of people suspected of having TB receiving TB services according to standards (suspects) only reached 60.36%, then the coverage of TB cases found for all new types reached 23.52%. Research Objectives: This is to know the management analysis of the Pulmonary Tuberculosis Control Program at the Labuhan Ratu Health Center. Research Methods: This study is a qualitative study with a phenomenological approach. The sampling technique used is snowball sampling with 8 informants who are directly related to the implementation of Pulmonary Tuberculosis Control Program. Data collection is done by observation, interviews, and documentation. Data analysis using reduction, material exposure, and conclusion. Results: Research shows that the management of the P2TB program has been going quite well, the obstacles still being are the human resources who still have double job, waiting chairs for infectious disease patients are still often used by general patients, there is no special service method for TB patients, the number of patients is reduced, the sputum quality is not good/dirty, and there is a lack of cooperation between cadres and the Health Center. Suggestions: Labuhan Ratu Health Center can make separate service flow for infectious disease patients especially Tuberculosis patients and pay more attention to who can use the particular waiting chair for effectiveness and reduce the risk of disease transmission.